Drug release from PLGA particles with polyelectrolyte coating - Nugraha, Chandra (2014)
PLGA is a traditional encapsulation matrix for drug release due to its biocompatibility and biodegradability, as well as release control manipulation through different physical parameters. Despite the versatility of PLGA, burst release remains a problem. It incurs unnecessary loss of drug, reduces period of sustained delivery, and causes potential overshoot of the drug's therapeutic window. It is known through the vast literature on PEM microcapsules that PEM film built on drug crystals serve as barrier to the releasing encapsulated drug. It has been applied to, commonly, liposomes, nanogels, and more recently PLGA nanoparticles. Fundamental studies of the release kinetics on systems with PLGA as the template, however, are lacking, as studies have generally been more focused on demonstration of PEM efficacy in surface functionalization, targeting, and cellular uptake. It is not known, therefore, how much PEM could control the drug release from PLGA. The objective of this study is therefore to determine the kinetics of drug release when PEM is applied on PLGA. This includes the conditions in which PEM functions as additional diffusional barrier to the drug release, and to determine the factors affecting such release. We managed to establish PEM on PLGA particles and films encapsulating both low and high MW drugs, with the aim of achieving release retardation. We monitored the drug loss during coating and confirmed a correlation between drug loss and release reduction. We also optimized the release curve in order to evaluate the release retardation, since certain shapes of the release curve would not enable analysis of the release retardation. Finally with the evidence of size dependence, we decreased the particle size and highlight the potential role of aggregation in release retardation. A mathematical analytical description was evaluated on the basis of Fickian diffusion, and the role of particle size is further explained. The novelty of the work stems from the fact that nobody has in detail probed the release kinetics of PLGA-PEM. All arrived at a conclusion that release is reduced, but without any further explanation of why such is the case, and how it relates to other parameters: the PEM built, the PLGA substrate, and the drug studied.